Students’ eating styles and palatable eating motives during the COVID-19 pandemic - Srisayekti, Wilis; Ancilla, Cecilia Joseph; Cahyani, Anggita Dian (Intelektual Pustaka Media Utama, 2024)
This study aimed to describe students’ driving factors of eating behavior, namely eating-styles and palatable-eating-motives, and to determine clusters based on both. Conducted during the COVID-19 pandemic, this cross-sectional study was carried out in response to the intervention program, the nusantara movement to reduce obesity rate (gerakan nusantara tekan angka obesitas (GENTAS)), launched by the Indonesian government to reduce obesity rate. Involving general population, 135 undergraduate students at a university in Bandung, Indonesia (the average age was 20.5 years, 71.9% of them were female) were selected using multi-stage-cluster-sampling. Data was collected through online questionnaires and was analyzed using SPSS 22.00 for Mac. Results indicated that participants’ eating behavior was generally more characterized by uncontrolled-eating-style, and participants’ eating palatable foods was more driven by the motive of reward-enhancement. This study obtained three clusters, including the cluster composed of emotional-eating-style and coping-motives, the cluster involving cognitive-restraint-eating-styles, and the cluster composed of uncontrolled-eating-style and all palatable-eating-motives. Findings about the clusters brought possibilities to develop new approach in eating behavior intervention for GENTAS’ implementation among students, focusing on tailored intervention based on the cluster of the individual participant, and utilizing the available channels at the institution. An online or hybrid intervention was an introduced choice that was relevant during COVID-19 pandemic and non-COVID period.